Analisis Komparasi Potensi Sektor Pariwisata Pulau Jawa dan Pulau Sumatera - Sekar Jati, Pangesti; Juliannisa, Indri Arrafi (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
The island of Sumatra and Java Island has excellent attractions and potential in the tourism sector that can improve the regional economy. This great potential needs to be developed to become a developed and developing tourism sector. This study was conducted with the aim of comparing the potential and attractiveness of the tourism sector on the island of Sumatra and Java Island, as well as the development of the tourism sector of Sumatra Island and Java Island. The analytical techniques used in this study are different tests, and sustainability analysis techniques using Micmac software. The results of this study are 1) in the different tests, there are differences in assessments by the people of Sumatra Island and Java Island, including community participation, the condition of tourist attractions, and road conditions; 2) this study classifies several variables that have been broken down from five variable clusters into four topologies, a) determinant variables that have a strong influence, namely infrastructure, and tourist attraction conditions, b) relay variables, namely the type of tourism, c) autonomous variables, namely natural conditions, surrounding conditions, and lodging places, d) dependent variables, namely road conditions, government participation, community participation, ecology, places to eat, and means